The Effect of Return on Assets, Debt to Equity Ratio and Current Ratio on Firm Value - Kevin Louis Jonathan; Sri Purwaningsih (PT. EQUATOR SINAR AKADEMIA, 2023)
This study aims to examine the effect of Return On Assets (ROA), Debt to Equity Ratio (DER) and Current Ratio (CR) on Firm Value. The object of this research is the transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. This research method uses a quantitative approach with a total sample of 60 companies and the analytical tool uses SPSS 25. The results show that partially the variables ROA, CR have a positive and significant effect on firm value as measured using Price Book Value (PBV), but DER has a significant negative effect on firm value.